Assessment of The Causal Link Between Undisclosed Medical Conditions and Death within The Scope of Insurance Law: A Case Series - İğde, Emre Nuri; Genç, Neslihan; Akçan, Ramazan; Balseven Odabaşı, Aysun (The Bulletin of Legal Medicine, 2025)
Personal loan-linked life insurance is widely used in our country. The insurance company is required to provide information, whereas the insured must reveal any pre-existing health conditions. After the death of the insured person, disagreements may emerge regarding undisclosed medical conditions. In such cases, courts frequently request expert opinions from forensic medicine specialists regarding the causal relationship between the undisclosed condition and the cause of death. This study analysed essential factors to evaluate causality in the lack of an autopsy. Four cases aged 47 to 69 were included in the study. A causal link was established between the undisclosed disease and death in two cases; in one case, causality could not be determined.  In another, the undisclosed illness was deemed a complication of a declared disease, thus not requiring separate disclosure. Forensic medicine specialists must evaluate the causality utilizing medical records, clinical findings, and the death certificate, while considering the certainty of the diagnosis.
Keywords: Forensic Medicine; Causal Link; Retrospective Assessment of Cause of Death; Life Insurance; Undisclosed Medical Conditions